Effective strategy for hybrid sensor networks in an unknown environment - ZHUANG Wei1; 2; SONG Guang-ming1 (Tongxin xuebao)
An effective strategy for hybrid sensor networks was proposed. It is designed to be used in an unknown envi- ronment. The system contains two-tier networks, sensor network and ad-hoc network. The coordination of two networks could enhance abilities in sensing, task executing, communication, etc. Meanwhile, simultaneous localization and naviga- tion acting as the important applications in hybrid sensor networks were illustrated in this paper. The flooding technique was adopted to deduce a path to the region of interest. A simple approach of video signal propagation as a significant ap- plication of the whole system was also presented. The received signal strength indicator was adopted to reflect the re- lationship between the sender and receiver. Also, the received signal strength of WiFi radio was employed to be a cri- terion for the movement of the robots. The real experimental results validate the feasibility and reliability of the pro- posed strategy.